2022
DOI: 10.1002/adma.202207152
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Magnetic Correlations in Frustrated Spinel ZnFe2O4

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adma.202207152. Magnetic materials with the spinel structure (A 2+ B 3+2 O 4 ) form the core of numerous magnetic devices, and ZnFe 2 O 4 constitutes a peculiar example where the nature of the magnetism is still unresolved. Susceptibility measurements revealed a cusp around T c = 13 K resembling an antiferromagnetic transition, despite the positive Curie-Weiss temperature determined to be Θ CW = 102.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…This large difference makes neutron data better suited for the robust determination of the degree of inversion compared with XRD. To establish the inversion, the occupancies were constrained such that all sites were fully occupied and that the overall composition matched the molar ratio, as determined by previously measured micro-X-ray fluorescence spectroscopy (XRF) (see ref ). When revisiting the XRF data, we found that a small error had led to the previously reported molar ratio of n Fe 2 O 3 / n ZnO = 1.06(2), while the correct ratio is in fact found to be slightly closer to ideal stoichiometry at 1.03(2) corresponding to the formula unit stoichiometry Zn 0.98(1) Fe 2.02(1) O 4 .…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…This large difference makes neutron data better suited for the robust determination of the degree of inversion compared with XRD. To establish the inversion, the occupancies were constrained such that all sites were fully occupied and that the overall composition matched the molar ratio, as determined by previously measured micro-X-ray fluorescence spectroscopy (XRF) (see ref ). When revisiting the XRF data, we found that a small error had led to the previously reported molar ratio of n Fe 2 O 3 / n ZnO = 1.06(2), while the correct ratio is in fact found to be slightly closer to ideal stoichiometry at 1.03(2) corresponding to the formula unit stoichiometry Zn 0.98(1) Fe 2.02(1) O 4 .…”
Section: Resultsmentioning
confidence: 85%
“…In the present study, we provide benchmark single-crystal ADPs for the archetypical spinel structure of ZnFe 2 O 4 , and we show that our crystals have limited defects (interstitials, inversion). It is exactly the defect-free nature of our samples that make them excellent for studying the frustrated magnetism in the system, since all the magnetic Fe atoms are located on the pyrochlore sublattice, which cannot support the antiferromagnetic order . The diffraction data were measured with high-energy radiation and to high resolution to avoid as many systematic errors as possible.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations